A Simple Synthesis of a High Gain Planar Array Antenna for Volume Scanning Radars - Tokan, F.; Gunes, F.; Turetken, B.; Surmeli, K. (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2012)
This paper describes a simple method of designing a rectangular planar array antenna with a flat top characteristic within the given 0 degrees <= phi <= phi(max) region in the theta = 90 degrees principal plane to be used in the volume scanning radars. In the method, the main beam of each ingredient linear array antenna is collimated to a predetermined direction with a permissible beamwidth within the total coverage region so that the superposition of the far field ingredient phasors can result in the required overall pattern with the flat top characteristic in the region of 0 degrees <= phi <= phi(max) the principle plane. The main beamwidth requirements of the sub-arrays are met by the excitation amplitudes determined by Dolph-Chebyshev analytical method. Furthermore, the overall main beam characteristic is improved by optimizing the excitation amplitudes using the genetic algorithm. The far field patterns resulted from the half-wave dipole and patch arrays are verified by using the full-wave simulation software, computer simulation technology (CST).
Keywords: Flat top pattern; linear sub-array; optimization; rectangular planar array; ALGORITHM; Engineering; Telecommunications